The Satisfaction of Civil Servants Civil Service Agency and Human Resources Development (BKPSDM) Bone Bolango Regency Through the Employee Welfare Program - Meylan Husain; Syamsinah; Ayu Anatasya Rachman (Journal of Economic, Business, and Administration (JEBA), 2022)
The current study aims 1) To identify and analyze the welfare program made by the government, especially the regional Government of Bone Bolango Regency at the Agency for Personnel and Human Resources Development of Bone Bolango Regency. 2) It also aims to find out and analyze the Saticfaction of the State Civil Apparatus Agency for Human Resources and Development of Bone Bolango Regency through the Employee Welfare Program. The method in this study uses descriptive qualitativ methods with interview and documentation data collection terchniques. The study results show that 1) welfare programs in the Staffing and Resource Development Agency of Bone Bolango Regency are in the form of Job Allowances, Employment BPJS Benefits, and Additional Employee Income Benefits (TPP). It also provides leave facilities work facilities that are adjusted to the class or position of each employee. 2) The Satisfaction of Civil Servants at the Personnel and Human Resources Development Agency of Bone Bolango Regency are already satisfied with the provision of a welfare program in the form of a salary adjusted to the class or position given by the Government every month in the form of a basic salary that does not experience deductions. It also provides allowances given according to the regulations set by the Government. In addition, employees will be given an award and work facilities to motivate employees to improve performance further.